Si Unyil Anak Indonesia - Tito Imanda (Antropologi Indonesia, 2004)
This article illustrates the process of reformulating Indonesian identities in the new "Si Unyil" program, decisions made, their background and consequences. The new Unyil appears for an ideal: parents miss an educational children television program. Production team seemed to believe that this ideal is not blocking their needs for profit. The question is 'who is the real audience?', 'Children or their parents?'. When reproduced, "Si Unyil" series is problematic. In one hand, the old Unyil is no longer fit the new television industry. Countryside setting is not interesting for the advertisement, so in the new series Unyil lives in a suburb area, place for middle class, the most potential market. Sarong and Malay's hat, wore by old Unyil, now are being replaced by unbuttoned shirt and backpack. The old Unyil played hide and seek and ate traditional cake, now Unyil plays videogame and eats ice cream. But this is an old legendary program for Indonesian children, how do they put the Indonesian context?